Pengaruh Model Pembelajaran Auditory Intellectually Repetition Terhadap Kemampuan Multi Representasi Matematis Siswa Smp - Wahyuni, Rika; Citroresmi.P, Nindy (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2019)
AbstractThis study aims to determine the effect of the AIR learning model on students' multi-mathematical representation abilities, student activities and learning motivation. The population of this research is all students of class VIII. Samples were taken by simple random sampling technique. The selected sample consisted of two classes, namely VIIIB as the experimental class and VIIIC as the control class. This research is an experimental research design with Pretest-Postest Control Gruop. The results of the study can be concluded that: (1) There is a difference in the ability of multi mathematical representation of students in the class using the AIR learning model and the class using the direct learning model. (2) The effect of the AIR model is relatively high on the ability of students' multiple mathematical representations; 3) student learning activities as a whole are classified as very active; 4) student motivation is categorized high.Â Keywords : Auditory Intellectually Repetition, multi representations, student activities, studentÂ  motivation